(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
Punta Manna Member is the younger unit of the Lower Cambrian Nebida Formation in southwestern Sardinia. Sedimentological analyses aim to characterize the type-section, formally and and briefly described by Rasetti in 1972. The sequence has been divided into three units on the basis of its lithological features. The lower unit (Oolitic Unit) mainly consists of Girvanella - archaeocyathan mounds alternated with oolitic grainstones and/or sandstones containing scattered accumulations of trilobite debris. The depositional setting corresponds to a littoral environment characterized by the alternated input of land and sea-derived sands, and where the mounds were periodically destroyed or buried by migrating sand waves. In the middle unit bioconstructions and archaeocyaths virtually disappear whereas trilobites were accumulated by currents and waves. Siliciclastic and oolitic sands prevail but are gradually replaced by quartzitic sands and early dolomitic muds. The appearance of these latter suggests a climatic trend towards arid condition in a depositional environment evolving to a tidal lagoon. In the upper unit the development of early dolomitic algal mats alternating with quartzitic sandstones, siltstones and shales, attests the establishment of a sabkha complex at first influenced by siliciclastic input coming from an arid continent. The low diversity of the fauna throughout the section appears to reflect the severe conditions of life resulting from the high variability in energy and salinity of the depositional setting.